Perceived coach-created empowering and disempowering motivational climate and moral behaviour in sport: mediating role of moral disengagement - Gürpinar, B.; Sari, I.; Yildirim, H. (Journal of Sports Sciences, 2023)
Based on Duda`s (2013) hierarchical and multidimensional conceptualization, this research integrates motivational climate dimensions from Achievement Goal Theory and Self-Determination Theory to investigate the constructs of empowering/disempowering motivational climates. We aimed to investigate the relationship between perceived coach-created motivational climate and prosocial-antisocial behaviours and determine whether moral disengagement mediated this relationship. 423 athletes completed self-reported questionnaires. The results showed that empowering motivational climate had a positive direct association with prosocial behaviour towards opponents/teammates. Disempowering motivational climate had a positive direct relationship with antisocial behaviour towards opponents/teammates. Also, disempowering motivational climate was indirectly related to antisocial behaviour towards teammates, antisocial behaviour towards opponents and prosocial behaviour towards opponents via moral disengagement. These findings suggest that athletes` perception of coach-created empowering motivational climate is likely to enhance athletes` prosocial behaviours, whereas athletes` perception of coach-created disempowering motivational climate may result in their higher antisocial behaviours which is mediated by moral disengagement. The findings emphasize the role of perceived coach-created motivational climates in athletes` moral behaviours, provide useful information on the mediating role of moral disengagement in this relationship and suggest practical implications for sports coaches, sports psychologists and sport executives who aim to create a positive sports environment for athletes.